A wide-band bandpass filter using a novel embedded short-circuited stub resonator - Singwong D. (2014)
This paper presents a wideband bandpass filter using an embedded short-circuited stub resonator. The resonator consists of a short-circuited stub placed inside the close-loop ring resonator functioning as the parallel circuits of inductor and capacitor. Therefore, its resonant frequency depends on loop dimension and the length of the stub. From the experiment, the resonator cell provides low return loss, sharp band rejection and the circuit size is much smaller than a quarter of wavelength. Then, the simple bandpass filter was designed at 2 GHz by using these resonators. It is found that the filter gives a fractional bandwidth (FBW) of more than 66% measured at the return loss of 20 dB and the insertion loss of less than 1 dB. Moreover, the measurement results are in good agreement with the simulation results. © 2010 IEICE Institute of Electronics Informati.